Significant intra-valvular pressure loss across EPIC SUPRA and perimount magna supra-annular designed aortic bioprostheses in patients with normal aortic size - Jagdish C. Mohan; Vishwas Mohan; Madhu Shukla; Arvind Sethi (Indian Heart Journal, 2017)
Doppler-derived trans-prosthetic gradients are higher and the estimated effective valve area is smaller than the catheter-derived and directly measured hemodynamic values, mostly due to pressure recovery phenomenon. Pressure recovery to a varying extent is common to all prosthetic heart valves including bioprostheses. Pressure recovery-related differences are usually small except in patients with bileaflet metallic prosthesis, wherein high-pressure local jets across central orifice have been documented since long back and also in patients with narrow aortic root. We describe two patients with normally functioning stented aortic bioprostheses with supra-annular design (EPIC SUPRA and PERIMOUNT MAGNA), wherein very high trans-prosthetic gradients and critically reduced estimated effective valve orifice areas in presence of normal aortic size were consistently recorded over long periods of follow-up. The valve leaflets, however had normal excursion, were thin, opened with a triangular or oblong shape and had expected geometric valve area (1.7 and 1.6 cm2 respectively) measured by 3D trans-oesophageal echocardiographic planimetry. Pressure recovery upstream the valves accounted for 20% and 12% of total pressure gradients respectively. Dominant site for pressure drop was intra-valvular (75–85%). Such a phenomenon has not been reported in vivo for these two valve designs.